2018
DOI: 10.11159/ehst18.116
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Hybrid Photovoltaic Devices Based On N-Type GaAs and Polymer Composites

Abstract: -Hybrid organic/inorganic solar cells have been fabricated and studied. The aim being to take advantage of the beneficial properties of both organic and inorganic materials. In this work we studied hybrid n-GaAs/Polymer photovoltaic devices and the effects of adding either carbon nanotubes or graphene into the polymer layer (either poly (3,4-ethyldioxythiophene):poly (styrenesulfunate) (PEDOT:PSS) or polyaniline (PANI)) to enhance its conductivity. We also investigated the use of two different metals (Al or Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…[115][116][117] However, reported PCEs of these types of hybrid devices are still very low (less than 1% [113,114,117,118] ) due to the moderate conductivity of PANI. The sole relative report with a higher PCE (2.75% [40] ) utilized composite materials by adding graphene nanoparticles (GNP) in PANI. Thus, the enhancement of conductivity is a key factor to improve the photovoltaic performance of these devices.…”
Section: Device Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[115][116][117] However, reported PCEs of these types of hybrid devices are still very low (less than 1% [113,114,117,118] ) due to the moderate conductivity of PANI. The sole relative report with a higher PCE (2.75% [40] ) utilized composite materials by adding graphene nanoparticles (GNP) in PANI. Thus, the enhancement of conductivity is a key factor to improve the photovoltaic performance of these devices.…”
Section: Device Structuresmentioning
confidence: 99%
“…[39] Thus, it is important to understand the factors that limit their performance so as to give full play to the advantages of both organic and inorganic semiconductor materials. According to the available reports, the factors that limit the performance of HSCs can be attributed to 1) mediocre electrical conductivity of the polymer layer, which can lead to nonradiative recombination; [40,41] 2) interface recombination between the inorganic semiconductor layer and the organic layer; [41] and 3) light reflectivity as a common problem of planar devices.…”
Section: Introductionmentioning
confidence: 99%
“…This research group has investigated the effect of employing two different metals (Al or Ag) on the efficiency of the solar cells. The achieved efficiencies for (PEDOT: PSS) and (PANI) were 4.41% and 1.4%, respectively (Salehi et al, 2018). In this work, the fabrication and electrical properties of Au/PANI/n-type GaAs hybrids solar cell grown on (100), (311)A, and (311)B n-type GaAs are presented.…”
Section: Introductionmentioning
confidence: 97%
“…Their study indicated that the crystallographic orientation of GaAs affects the electrical properties of the device. Furthermore, the most recent study about the hybrid photovoltaic device based on n-GaAs and conducting polymer PANI was carried out in 2018 by Salehi et al (2018). This research group has investigated the effect of employing two different metals (Al or Ag) on the efficiency of the solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain thin film in either micro or nanoscale, commonly Physical Vapor Deposition (PVD), Chemical Vapor Deposition (CVD) and spin-coating techniques are used [1 -3]. Spin coating is recognized as the most common technique that can be applied for the deposition of different materials in the form of solutions such as nanoparticles, polymers and biomaterials [4]. Also, it is the most convenient technique for fabricating hybrid solar with different thin film thicknesses.…”
Section: Introductionmentioning
confidence: 99%